PERNIKAHAN BUGIS-MELAYU DAN CIKAL BAKAL GELAR BARU KEBANGSAWANAN DI KERAJAAN JOHOR RIAU - Rahmat, Syahrul; Idi, Abdullah; Syawaludin, Mohammad (Handep: Jurnal Sejarah dan Budaya, 2023)
Internal conflict in the struggle for power within the Kingdom of Johor in the 18th century involved the Bugis people in the area. The Upu Daeng Brothers earned the Yang Dipertuan Muda (YDM) in the Kingdom of Johor, married Malay nobles and the sultan's sister after they successfully conquered Raja Kecik. Accordingly, these situations led to the disappearance of Bugis person’s identity. In other words, Bugis descent who marry Malays no longer bear the name Daeng but Raja. The study employed historical research methods applying heuristics, source criticism, interpretation, and historiography, in which the data analysis was from the perspective of the cultural identity approach. This research revealed that the Bugis descent who lived and settled in the Johor Riau Kingdom since the 18th century were known as Bugis Malays. The new identity was due to the title 'raja,' bestowed upon the Bugis who married the Malays. The use of the new title began with the involvement of Bugis descendants in government and marriages between Bugis and Malay aristocrats.